Synthesis and properties of thermally reduced graphene oxide/polyacrylonitrile composites - Lee, Sungho; Kim, Yang-Jin; Kim, Do-Hwan; Ku, Bon-Cheol; Joh, Han-Ik (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Graphene oxide (GO) was prepared from graphite using a modified Hummers method. The GO dispersed in dimethyl sulfoxide (DMSO) was incorporated into polyacrylonitrile (PAN) dissolved in DMSO to prepare composite films using a conventional solution-casting method. DSC results showed a significant decrease in the cyclization temperature of polyacrylonitrile (PAN) in the presence of GO because the functional groups of GO initiated cyclization at lower temperature by an ionic mechanism. Heat treatment in air at 250 degrees C for 3 h led to stabilization of PAN and a simultaneous partial reduction of GO. A significant decrease in the electrical resistivity of the GO/PAN composite films was observed because the partially reduced GO acted as a conducting filler. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: CARBON; POLYACRYLONITRILE; STABILIZATION